Penerapan Prinsip Arsitektur Bioklimatik Dalam Perancangan Tropical Orchid Centre - Mhd. Romi Firmansyah; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Orchid grows and estimated has 5.000 species in Indonesia. However, nowdays there are many human activities, inflicting a destruction of ecosystem, which resulting a lessening orchid’s habitat species. Conservation is needed to maintain the continuity of species of orchids. The design of conservation center to be developed is Tropical Orchid Center that serves as nature tourism, education, and research. Since influenced by good climate, the capacity of sunlight, air humidity, and air temperature, the Bioclimatic Architecture will be applied to the design of this Tropical Orchid Center. The concept of "Walk in The Rainforest” is applied to the site design, the shape of the building, the facade, and the landscape.Keyword: Orchid, Tropical Orchid Center, Walk in The Rainforest